Developing Teaching-Learning Model To Enhance Autonomous Ptkin Learners - Fathor Rasyid (Didaktika Religia, 2021)
The study is intended to develop a teaching model to foster Indonesian students to be autonomous learners. The study is participatory action research with mixed method. The research subjects were English department students of State Islamic Institute (IAIN) Tulungagung and IAIN Kediri taking Writing 1. The instrument was adapted from established instrument to meet the purpose of the study. Quantitative data were analyzed through correlated t-test and repeated measure ANOVA, while qualitative data were analyzed through thematic content analysis. There were eight stages in the study: identifying needs, setting goals, planning learning, selecting resources, selecting learning strategies, practice, monitoring progress, and assessment and revision. These all stages were designed and determined together by the teachers and students. The results reveal that there are four main stages to enhance the students’ autonomy in writing. The first is free writing in which the students wrote a paragraph freely on any topic they liked. Having finished this first draft, they were to self-check their own work based on some criteria provided. The second is peer correction in which they exchanged their own work to their peers (peer correction) in order to gain some suggestion, correction, and comments. The third is edited free-writing. Having got some suggestion, correction, and comments from peers, they started to revise their own work. The last is final copy. Inthis stage, they were to have final self-check. Statistical analysis also reveals that this strategy significantly increases the students’ learning autonomy.